Psychospiritual Interventions and Mental Health: A Recent Comprehensive Review - Mohd Sobri Ellias; Mohd Zohdi Mohd Amin; Mohd Asyran Safwan Kamrzaman; Mohd Manawi Mohd Akib; Mohd Zahir Abdul Rahman; Muhammad Akmalludin Mohd Hamdan; Ahmad Mutawalli Mustaffha (Global Academic Excellence (M) Sdn Bhd, 2026)
Tier 3- Indexed by MyCite